Bryoflora and moss vegetation of national nature parks of Ukrainian Forest-Steppe zone (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The bryoflora and moss vegetation of national nature parks «Podolski Tovtry» (Khmelnytsky region), «Ichnyansky»(Сhernigiv region) and «Homolshanski forests» (Kharkiv region) are characterized. A classification scheme of moss vegetation of natural reserves studied in the region is given.
Keywords: mosses, Ukrainian Forest-Steppe, bryocommunity, bryocoenotic, ecologofloristic classification, national parks.